Effects of Exposure to Heat Stress During Late Gestation on the Daily Time Budget of Nulliparous Holstein Heifers - Toledo, Izabella M.; Ouellet, Veronique; Davidson, Brittney D.; Dahl, Geoffrey E.; Laporta, Jimena (Frontiers in Animal Science, 2022)
Exposure of dairy cows to heat stress negatively affects welfare and performance during the lactation cycle. While we understand how mature cows respond to heat stress, the effects of late gestation heat stress on pregnant heifers are still unknown. Automated monitoring devices were used to document the behavioral activity of heifers during the pre- (final 60 d of gestation) and postpartum (first 60 d of lactation) periods. Pregnant Holstein heifers (n=25) were housed in a free-stall barn and enrolled to heat stress (HT; shade; n=13) or cooling (CL; shade, soakers and fans; n=12) treatments during the last 60 days of gestation. All animals were actively cooled postpartum. Upon enrollment, heifers were fitted with a leg tag, which measured daily lying time, number of steps, and standing bouts, and a neck tag that measured eating and rumination times. Rectal temperatures (RT) and respiration rates (RR) were measured thrice weekly during the prepartum period. Relative to CL, HT heifers had elevated RT and RR during the prepartum period. Heat-stressed heifers tended to spend more time eating (224 vs. 183 min/d) and less time ruminating (465 vs 518min/d) during the prepartum period compared to CL, but dry matter intake did not differ. During the postpartum period, HT heifers spent more time eating (209 vs. 180 min/d) during weeks 1 to 4 of lactation. Rumination time was similar. Lying time was reduced by 59 and 88 min per day during weeks -7 and -6 prepartum and 84 and 50 min per day during weeks 2 and 3 postpartum in HT heifers. The number of steps was greater for HT during the postpartum period, from weeks 2 to 9 (3019 vs. 2681 steps/d). Eating frequency was similar during pre- and postpartum periods, however, HT consumed larger meals at night during the pre- and postpartum periods compared with CL heifers. In summary, late-gestation exposure to heat stress affects the daily time budget of first lactation heifers during both the pre- and postpartum periods. The current insights may contribute to the development of more effective management strategies to mitigate heat load.